Embedded Librarian in Higher Education Institutions - Ibrahim, Shahril Effendi; Omar, Fazli (2015)
The roles of librarians in this modern and ubiquitous digital information era have been changed. The new environment of abundant and ubiquitous information offers librarians to provide a new mode of librarianship. This paper intends to discuss on the concept of embedded librarianship particularly in higher education institutions. The driving factors and attributes of embedded librarianship will be also discussed. The role of embedded librarians in higher institutions will be also explained. Sustaining embedded librarian in organisation and embedded librarian in distance education environment will be also discussed. Finally, a practice of embedded librarian in Dar al-Hikmah Library in International Islamic University of Malaysia (IIUM) will be briefly highlighted in this paper.